Innovative Corporate Style Flip E Module for Teaching Contemporary Issuesin Islamic Education - Nur Aini; Nurul Zainab; Moh. Hamzah; Ummi Kalsum (Universitas Bumigora, 2026)
The increasing adoption of digital technology in higher education requires instructional materials that are interactive, flexible, and capable of supporting independent learning. This study aimed to develop and evaluate the feasibility and effectiveness of a Flip PDF Corporate Edition-based e-module for teaching Religious Moderation in the Contemporary Issues in Islamic Education course. The study employed a Research and Development (R&D) approach using the ADDIE instructional design model. The e-module was validated by content, media, and language experts and subsequently implemented with sixth-semester studentsof the Islamic Education Study Program at STIT Aqidah Usymuni Sumenep. Data were collected through expert validation sheets and student response questionnaires and analyzed using descriptive percentage analysis. The expert validation yielded an overall feasibility score of 96.67%, classifying the e-module as Very Feasible, while the implementation phase produced an effectiveness score of 92.46%, indicating a Very Good level of effectiveness. Students reported high levels of engagement (90.18%), content comprehension (91.67%), and language clarity (91.67%), demonstrating that the integration of multimedia elements, interactive assessments, and browser-based accessibility effectively supported learning. The findings indicate that the e-module enhances student engagement, facilitates conceptual understanding, and promotes self-directed learning in technology-enhanced learning environments. This study contributes to the growing body of research on digital learning by providing an empirically validated multimedia e-module that integrates formative and collaborative assessment strategies to support the teaching of Religious Moderation in higher education. The developed e-module offers a practical instructional model for educators seeking to integrate interactive digital learning resources into Islamic Education.